Benthic Dinitrogen Fixation Traversing the Oxygen Minimum Zone Off Mauritania (NW Africa) - Gier, Jessica; Löscher, Carolin R.; Dale, Andrew W.; Sommer, Stefan; Lomnitz, Ulrike; Treude, Tina (Frontiers in Marine Science, 2017)
Despite its potential to provide new nitrogen (N) to the environment, knowledge on benthic dinitrogen (N2) fixation remains relatively sparse and its contribution to the marine N budget, is regarded as minor. Benthic N2 fixation is often observed in organic-rich sediments coupled to heterotrophic metabolisms, such as sulfate reduction. In the present study, benthic N2 fixation together with sulfate reduction and other heterotrophic metabolisms were investigated at six station between 47 and 1108 m water depth along the 18°N transect traversing the highly productive upwelling region known as Mauritanian oxygen minimum zone (OMZ). Bottom water oxygen concentrations ranged between 30 and 138 µM. Benthic N2 fixation determined by the acetylene reduction assay was detected at all stations with highest rates (0.15 mmol m-2 d-1) on the shelf (47 and 90 m water depth) and lowest rates (0.08 mmol m-2 d-1) below 412 m water depth. The biogeochemical data suggest that part of the N2 fixation could be linked to sulfate- and iron-reducing bacteria. Molecular analysis of the key functional marker gene for N2 fixation, nifH, confirmed the presence of sulfate- and iron-reducing diazotrophs. High N2 fixation further coincided with bioirrigation activity caused by burrowing macrofauna, both of which showed high rates at the shelf sites and low rates in deeper waters. However, statistical analyses proved that none of these processes and environmental variables were significantly correlated with benthic diazotrophy, which lead to the conclusion that either the key parameter controlling benthic N2 fixation in Mauritanian sediments remains unidentified or that a more complex interaction of control mechanisms exists. N2 fixation rates in Mauritanian sediments were 2.7 times lower than those from the anoxic Peruvian OMZ.